Influencer marketing and the purchasing decision of millennial consumers in a retail company in Cajamarca, 2025 - Alfaro Mendoza, Diana Alexandra; Vargas Miranda, Gabriela Sugey; Samán Chingay, Saraí Nelly; Chávez Lezama, Leyla Michelle (LACCEI, 2025)
The purpose of this research was to analyze the relationship between influencer marketing and the purchase decision of millennial consumers in a retail company in the city of Cajamarca in the year 2025. This research arises from the growing relationship of social networks in consumer behavior, especially in the millennial generation. Regarding the methodology, it was a basic type of research, with a non-experimental and cross-sectional design; correlational scope and quantitative approach. The sample was made up of 383 millennial consumers, selected through Simple Random Sampling. The results obtained indicated that there is a very high positive correlation between influencer marketing and the purchase decision, with a significance level of 0.000 < 0.05 and a Spearman's Rho coefficient of 0.976. This shows that, the greater the perceived relationship of influencers on social networks, the greater the probability that consumers will make a purchase. In this way, it is concluded that influencer marketing plays an important role in the purchasing decision process of millennial consumers in the context of a retail company in Cajamarca.